Development of a Test Design for Sprint Talent Selection - Suratmin; I Putu Darmayasa; Ni Putu Vivin Indrawati; Hanik Liskustyawati; Daniel Womsiwor; Lintang Hilmi Mumtaz Surath (Mimbar Ilmu, 2025)
Currently, sprint coaches do not yet have a standardized reference or guideline as a parameter for recruiting talented prospective athletes. This study aimed to develop a sprint sports talent selection test instrument for elementary school students. The research employed a research and development (R&D) approach with stages including needs analysis, design, and field trials. Data were collected through literature review, interviews with coaches, and discussions with athletics experts. The developed instrument consisted of anthropometric and biomotor tests. Data analysis was carried out through content validity testing by experts, as well as construct validity and reliability testing using statistical procedures. The results showed that among male students (N = 11), no participants were categorized as highly talented (0%) or untalented (0%), with 25% categorized as talented, 53.41% as moderately talented, and 21.59% as less talented. Among female students (N = 8), 4.69% were categorized as highly talented, 20.31% as talented, 60.94% as moderately talented, 14.06% as less talented, and 0% as untalented. This distribution reflects variations in sprinting ability among students, with the majority falling into the moderately talented category. It can thus be concluded that the developed sprint talent selection test instrument effectively maps the potential of elementary school students in an objective and measurable manner. These findings provide a strong foundation for coaches and educational institutions in identifying, training, and developing young athletes more effectively from an early age.